Emotional Intelligence as a Mediator between Teachers’ Emotional Mistreatment and Long-Term Emotional Impact on Students - Anantha Raj A. Arokiasamy (Zien Journals, 2021)
Teacher emotional mistreatment, which includes both verbal and nonverbal abusive behaviors, is a widespread and harmful experience for school students. However, its long-term emotional impacts remain relatively unexplored. This study explored the mediating role of emotional intelligence (EI) on the association between teacher’s emotional mistreatment towards school children and the long-term emotional impact on the students. A total of 297 Malaysian Muslim students in different stages of their university training completed the Psychological Maltreatment Subscale Questionnaire on teacher’s mistreatment while they were in school, and the Wong and Law EI Scale. The long-term emotional impact was measured using a tool developed especially for the study. Results revealed that 36% of the participants reported being mistreated by teachers at least once. The most reported long-term emotional impacts were feeling defensive, feeling a constant need to prove their worth, and fearing not to be perceived as lazy. Teacher mistreatment had significant long-term emotional impacts and was negatively correlated with EI. EI further acted as a significant mediator in the links between teacher mistreatment and its long-term emotional impact, with an indirect effect of .032. Raising awareness among teachers as to possible long-term emotional effects of abusive behaviors may help decrease mistreatment in the future. Determining the long-term impact of emotional mistreatment on social-emotional skills can help explain and prevent various types of negative outcomes in those students at a later stage in life.
Keywords: Emotional Intelligence (EI); Long-Term Emotional Impact; Emotional Mistreatment; Teacher Behavior